‘God’s foreign policy’: Christian Zionism and religious diplomacy in Africa - Dadoo, Suraya (Religion, state & society, 2025)
This contribution explores the extent to which Christian Zionist theology emanating from politically influential Pentecostal churches and the born-again movement in the Democratic Republic of the Congo (DRC), Ghana, and Malawi has influenced diplomacy in relation to Israel at the United Nations and African Union. It is argued that the strategies employed by the Israeli government to grow the Christian Zionist movement in the United States, which have shaped Washington’s foreign policy towards Israel, have been exported to Africa. It is found that although Israel’s Christian Zionist religious diplomacy initiatives in Africa have made significant inroads into a continent traditionally sympathetic to Palestine, there are limits to this success.